2017
DOI: 10.1007/s12274-017-1464-z
|View full text |Cite
|
Sign up to set email alerts
|

Gallium bismuth halide GaBi-X2 (X = I, Br, Cl) monolayers with distorted hexagonal framework: Novel room-temperature quantum spin Hall insulators

Abstract: Quantum Spin Hall (QSH) insulators with a large topologically nontrivial bulk gap are crucial for future applications of the QSH effect. Among these, group III-V monolayers and their halides with chair structure (regular hexagonal framework, RHF) were widely studied. Using first-principles calculations, we propose a new structure model for the functionalized group III-V monolayers, which consist of rectangular GaBi-X 2 (X=I, Br, Cl) monolayers with a distorted hexagonal framework (DHF).These structures have a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 106 publications
(197 reference statements)
2
7
0
Order By: Relevance
“…The slope of the band close to the Dirac point P is indicated by S and a similar label can be applied to Q/P'/Q'.From the Dirac point with linear bands, we can calculate the Fermi velocity (v F ) by a linear fitting of the first-principles calculations date. Because the Dirac points are not at the high symmetry points, the double Dirac points can be regarded as two distorted Dirac points, which is similar to that in phagraphene 10 /distorted GaBi-X 2 monolayers (X = I, Br, Cl)60 /YN 2 . 61 In general, the distorted Dirac point has two different Fermi velocities along the high-symmetry line directions.…”
mentioning
confidence: 89%
“…The slope of the band close to the Dirac point P is indicated by S and a similar label can be applied to Q/P'/Q'.From the Dirac point with linear bands, we can calculate the Fermi velocity (v F ) by a linear fitting of the first-principles calculations date. Because the Dirac points are not at the high symmetry points, the double Dirac points can be regarded as two distorted Dirac points, which is similar to that in phagraphene 10 /distorted GaBi-X 2 monolayers (X = I, Br, Cl)60 /YN 2 . 61 In general, the distorted Dirac point has two different Fermi velocities along the high-symmetry line directions.…”
mentioning
confidence: 89%
“…First, the SOC effect is related to the element type: the heavier the element, the more pronounced the SOC effect becomes. Structures including heavy elements, such as Bi, can have a large SOC effect [55,56]. Second, the SOC effect is also related to the atomic orbitals forming the Dirac cone.…”
Section: Band Structurementioning
confidence: 99%
“…33,34 Monolayer GaBiCl 2 , ZrBr and HfCl were identified as room-temperature quantum spin Hall insulators with large nontrivial band gaps. 35,36 FeCl 2 displays a half-metallic ferromagnetic ground state. 37,38 Recent experimental studies demonstrated that single crystals of CrI 3 can be cleaved very easily, possess a ferromagnetic order even in the monolayer form, and are stable in air/water, in the absence of CrI 2 contamination.…”
Section: Introductionmentioning
confidence: 99%